(untitled) (Journal of Geography and Environmental Management, 2018)
The rivers of the Buktyrma Basin cross many roads, residential houses, household outbuildings and other structures are located on their coastline area. Along the river valleys, at a considerable distance, there are railroads, highways, communication and power lines, hydrotechnical and hydro-reclamation facilities. Erosion processes associated with the action of permanent and temporary watercourses in river valleys of Buktyrma Basin are actively manifested near road sections and bridge crossings. Analysis of the dynamics of erosion processes and assessment of the current state of erosion of territories in the valley of the Buktyrma River are urgent tasks both from a scientific and a practical point of view. Investigation of the dynamics and modern condition of dangerous channel and erosion processes in the Buktyrma river basin allow us to give a forecast of the deformations of river beds, which is very important in the design of erosion control measures and general plans of populated areas in conditions of complicated hydrological situations. The article presents the results of a study of dangerous manifestations of channel and erosion processes in the Buktyrma river basin near road sections and bridges. Examples of revealing from the space images washed out river banks and their morphometric characteristics are shown. As a result, active development of erosion processes are identified in 46 sections of rivers. The locations and levels of danger that are susceptible to the destruction of sections of roads and bridges are determined and plotted on the hypsometric map of the Buktyrma river basin.